Peran Keterlibatan Orang Tua dalam Membentuk Perilaku Anak melalui Kegiatan Sekolah Sabat Kelas Kindergarten di Gereja Masehi Advent Hari Ketujuh Jemaat Kedaton - Sitorus, Panahatan; Hendriks, Alvyn Cesarianto (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research comprehensively explores the influence of parental involvement in shaping children's behaviour through sabbath school activities in the Kindergarten class of the Seventh-day Adventist Church of Kedaton Lampung, with the research methodology applied is a qualitative method and literature study and exploration of suitability from the perspective of being a parent. Data were obtained through in-depth analysis of various literature sources. The findings of this study unequivocally state that an understanding of the role of parents in parental involvement, behaviour formation and kindergarten sabbath school activities are very important elements to achieve the child's life goals. In addition, this study illustrates the dynamics of behavioural change that forms its own perspective regarding the education of children. The implications of the findings provide a deep understanding of the needs and challenges faced by parents in shaping behaviour through Spiritual activities in the life of worship.